Makna Komunikasi Orangtua dan Anak dalam Film Animasi - Salma Luthfia Adriana; Moh. Subur Drajat (UNISBA Press, 2023)
Abstract. Film is a form of audiovisual work that is arranged so as to form a story that can be enjoyed and becomes a medium of communication through symbols and message systems. Film is a field of study that is relevant for semiotic analysis, because it is built with many diverse signs and works together to achieve the desired effect. In the process of communication, film can be used as a mass medium to convey messages through signs that form meaning.